SUSTAINABLE AGRICULTURE AND CLIMATE RESILIENCE: THE ROLE OF AGROECOLOGY IN MITIGATING ENVIRONMENTAL DEGRADATION - Yusuf Sani (Modern American Journals, 2025)
Agriculture is both a contributor to and a victim of climate change, facing significant challenges in maintaining food security and livelihoods while mitigating environmental degradation. The increasing unpredictability of weather patterns, soil depletion, and biodiversity loss exacerbate the pressures on farming systems. Agroecology, an integrated approach that combines agricultural production with ecological principles, has emerged as a promising solution for addressing these challenges. This paper explores the role of agroecology in enhancing climate resilience and sustainability by focusing on the application of ecological principles in farming systems. We analyze how agroecological practices can mitigate soil erosion, improve water retention, reduce dependence on synthetic inputs, and enhance biodiversity, thus fostering long-term environmental sustainability. Drawing on case studies and current research, the paper evaluates the potential of agroecology in contributing to climate change mitigation and adaptation, particularly in developing regions most vulnerable to the impacts of climate change.
Keywords: Sustainable Agriculture, Agroecology, Climate Resilience, Environmental Degradation, Climate Change Mitigation, Soil Health, Biodiversity, Agricultural Practices, Food Security, Ecosystem Services.